(untitled) (CIPEEX, 2025)
This work explores the theoretical foundations of structural decisions, presenting them as essential mechanisms for reorganizing social, political, and institutional systems in situations of systemic violations of fundamental rights. The objective is to distinguish structural processes from traditional collective actions, emphasizing their unique features such as complexity, multipolarity, prospectivity, and institutional recomposition. The method applied is theoretical and comparative, analyzing case law from Brazil and abroad, with particular reference to the Brazilian environmental litigation of the coal industry and the landmark U.S. precedent Brown v. Board of Education. The analysis demonstrates that structural processes require the judiciary to adopt a proactive and prospective role that goes beyond the binary logic of ordinary adjudication, demanding continuous monitoring, cooperation with other branches of government, and an openness to social participation. The results show that structural decisions, when properly implemented, foster the creation of long-term policies and institutional reforms that directly address the root causes of systemic problems, ensuring not only the recognition of rights but their effective realization. The conclusion highlights that structural decisions represent an innovative procedural tool within the Brazilian legal system, capable of promoting social justice, consolidating constitutional effectiveness, and protecting human dignity in complex and multipolar disputes, even though they still face challenges such as political resistance and the need for specialized judicial expertise.